A Walk around Irkutsk’s Quarters - Grigoryeva, Elena (project baikal, 2015)
The article presents the key issues of the Concept of reconstruction of the 11 Irkutsk’s quarters adjacent to the Trading Axis. While remaining basic, the trading function should reduce its overwhelming domination to be in harmony with other functions of the city environment, which attract inhabitants and guests to the historical area of Irkutsk, that is culture, education, leisure, recreation, and housing.